Analysis of the Influence of Transformational Leadership on Organizational Citizenship Behavior of Professional and Non-Professional Staff in Hospitals - Efendi, Efendi; Siregar, Liper; Nainggolan, Anju Bherna D.; Sherly, Sherly; Sudirman, Acai (International Journal of Business, Law, and Education, 2024)
This study aims to analyze the effect of transformational leadership on organizational citizenship behavior (OCB) in professional and non-professional staff in hospitals in North Sumatra. The research method uses a quantitative approach by distributing questionnaires to professional and non-professional staff working in several hospitals in North Sumatra. Data analysis was carried out using the regression method to see the significance of the effect of transformational leadership on OCB in both groups of respondents. The number of samples used was 190 respondents, as determined by the convenience sampling method. The study's results confirmed that transformational leadership positively and significantly affects organizational citizenship behavior. The results of this study are expected to contribute to hospital management in designing effective leadership strategies to encourage increased OCB. The right transformational leadership style can increase workforce engagement and overall hospital performance.